2014
DOI: 10.4314/star.v3i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of <i>Polyalthia longifolia</i>, <i>Anaphalis lawii</i> and <i>Gnidia glauca</i> against Colletotrichum <i>capsici</i> and Urinary Tract Pathogens

Abstract: Article InformationThe present study was conducted with an aim of determining inhibitory effect of extracts from different parts of Polyalthia longifolia (leaf, ripe and unripe pericarp), Anaphalis lawii (leaf and flower), Gnidia glauca (leaf, bark and flower) against Colletotrichum capsici and urinary tract pathogens. The shade dried plant materials were extracted using methanol. Antifungal effect of extracts was evaluated against Colletotrichum capsici isolated from anthracnose of chilli by Poisoned food tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Similar result was observed in our previous study in which the leaf and pericarp extracts showed inhibition of C. capsici isolated from anthracnose of chilli. The unripe pericarp extract inhibited C. capsici to higher extent when compared to leaf and ripe pericarp extracts which displayed similar inhibition of the fungus 24 . It has been shown that leaf extract exhibited marked growth inhibition of S. rolfsii causing collar rot of lentil 42 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similar result was observed in our previous study in which the leaf and pericarp extracts showed inhibition of C. capsici isolated from anthracnose of chilli. The unripe pericarp extract inhibited C. capsici to higher extent when compared to leaf and ripe pericarp extracts which displayed similar inhibition of the fungus 24 . It has been shown that leaf extract exhibited marked growth inhibition of S. rolfsii causing collar rot of lentil 42 .…”
Section: Discussionmentioning
confidence: 80%
“…In an earlier study, leaf and pericarps extract exhibited stronger inhibition of Gram positive uropathogenic bacteria viz., S. aureus and Enterococcus faecalis when compared to Gram negative uropathogenic bacteria. Unripe pericarp displayed stronger inhibition of uropathogens followed by ripe and leaf extracts 24 . A clerodanediterpenoid isolated from leaves inhibited S. aureus to higher extent than Gram negative bacteria 15 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The active extracts showed a high total phenolic (126.25 ± 0.20 µg GAE/ mg) and flavonoid (25.75 ± 0.10 µg CE/mg) content [3]. G. glauca bark extract is reported to have superior antibacterial activity against urinary tract infection causing pathogens like Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus faecalisas compared to leaf and flower [4].…”
Section: Antimicrobial Activitymentioning
confidence: 99%